Social media and their relations with the political changes in the Arab Region Concepts and dimensions study - djeddi, radouane; kihoul, taleb (Journal of Social Sciences and Humanities, 2020)
the narrative personal framework... Based on these data, we are trying to monitor the difficulties of influencing social networks in Algeria, in contrast to the role they played in Tunisia or Egypt, which is due to the fact that many users of these networks have narcissism and their self-interest is limited to presenting its form in a good image, as the political obsession is very weak for Algerian bloggers. وسائل اإلعالم اإلجتماعية وعالقتها بالتغييرات السياسية في ا ملنطقة العربية :دراسة في ا ملفاهيم واألب عاد 13 In the end, it is a crucible for gaining experience and achieving self through dealing with the other. In addition, through this study, we discover the challenges facing users such as respecting the right of privacy and not using them in spying, stealing private information and bank data, threaten the values of society, such as publishing sex images. "The personal information of Algerians is not only used in intelligence activities, but also extends to criminal networks that use the Internet as a weapon to carry out various crimes, foremost among which are information related crimes."